Accelerating growth : best practices in competitiveness strategy 2011 (Global Federation of Competitiveness Councils Washington, D.C.US, 2011)
Outlines best practices ranging from profound policy shifts, such as fundamental changes in the Middle East in the wake of the Arab Spring, to strategies for innovation-lead growth, to the creation of industries that harness the economic power of natural resources.
Keywords: ECONOMIC GROWTH